Economic geographies of rhe urban system: top-down, bottom-up trajectories of development and change in Dublin's inner city - Punch, Michael (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
The aim of this paper is to examine some top-down and bottom-up aspects of recent processes of economic development and transformation. as these have played out across Dublin 's inner city. In particular. the paper offers an overview of the impacts of recent restructuring processes linked to the globalisation of capital and a theoretical-practical ex plorat ion of the construction of a putative 'social economy' in the inner city over recent years. This has seen increasing involvement of community activists. traditionally attachcd to independent grassroots associations promoting the interests of specific urban locales. in the creation and management of bottom-up economic interventions. The intention at this point is to 'map' this emergent territory, raising some critical questions for further research regarding its place and meaning.
Keywords: Urban geography -- Ireland